(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to explore "the relationship between job satisfaction and job belonging among employees in the General Education Department in Al-Rusafa II - Baghdad". To achieve this, a scale consisting of (15) paragraphs was developed. These paragraphs were combined into a functional scale consisting of (26) distinct paragraphs, each prepared by the researcher. The psychometric properties of the scale were evaluated using a random sample of (100) males and females. The results indicated that the sample showed both job satisfaction and job belonging, revealing the existence of a statistically significant positive relationship between the two. The research results were used to propose recommendations and proposals...